Age Limitations for Presidential and Vice Presidential Candidates Post Constitutional Court Ruling Number 90/PUU-XXI/2023 A Democratic Perspective - Delfina Gusman; Pascoal da Costa Oliveira (Jurnal Hukum dan Peradilan, 2023)
The constitutional right to vote or be elected is a realization of a democratic government system. Freedom exists for every citizen or government to be able to participate in the advancement of a nation. Nominating the head of state in Indonesia is a big part of political participation for every citizen nominated by their political party to be able to run for president. However, in Indonesia, certain conditions must be met for citizens running for President, one of which is a minimum age limit. This age restriction became an academic debate until the Petitioner was tested at the Constitutional Court, where he had potential disadvantages, namely not being able to run for president even though he had experience or expertise in the world of government. This research is legal research with towards statutory case analysis. The results of this research explain that the age restrictions for presidential nomination requirements in Indonesia are not only bound by formal provisions, but the Court provides an alternative consideration regardless of the age of a presidential candidate who can nominate if they have experience or are currently serving as regional heads. The implications of the Constitutional Court's Decision Number 90/PUU-XXI/2023 regarding the alternative in the form of age quality for Presidential candidacy wishes of the Community in performing theirÂ  political rights